Integrated mechanisms underlying heat-induced disease susceptibility to pathogens in Arabidopsis and crops - Rodriguez H., Bladimir X., author; Argueso, Cris, advisor; Leach, Jan, committee member; Reddy, Anireddy, committee member (Colorado State University. Libraries, 2025)
Climate change and rising temperatures subject plants to heat stress, which reduces their growth and yield and renders them more vulnerable to pathogen attacks. This increased susceptibility primarily results from the detrimental effects of heat stress on plant immune responses, via disruption of defense signaling pathways and decreased production of protective compounds, such as secondary (selective) metabolites. Hence, the plants become more susceptible to infection by several pathogens. This phenomenon is referred to as Heat-Induced Disease Susceptibility (HIS) and is emerging as an important topic in plant biology, especially in the context of climate change. Here, I ask whether the phytohormone cytokinin, a coordinator of growth, source-sink allocation, and defense, links warm temperatures to a more permissive apoplast for bacterial pathogens. Using Arabidopsis thaliana-Pseudomonas syringae pv. tomato DC3000 as a model, I first show that early immune signaling diminishes at high temperature (HT) in both Col-0 and the CK-receptor double mutant ahk2,3: flg22-triggered MPK3/6/4 phosphorylation was robust at room temperature but reduced at HT, showing no enhancement in ahk2,3, arguing against "stronger defense" as the basis for its lack of HIS. I then reanalyzed previous RNA-seq and found that HT suppresses SA/SAR and other defense programs in both genotypes, again pointing away from preserved immunity and toward metabolism/nutrition as the differentiator. To probe that axis, we profiled apoplastic wash fluid by untargeted GC-MS across Genotype × Temperature × Inoculation and analyzed normalized intensities with a mixed-effects model (pre-specified contrasts). We retained 139 metabolites, tested 8 contrasts per metabolite (1,112 tests), and observed 129 significant metabolite–contrast effects (Tukey-adjusted). HT depleted simple sugars while ahk2,3 showed reproducible BCAA (valine, isoleucine) enrichment, with or without pathogen, consistent with a low-sugar, branched-chain amino acids (BCAA)-enriched apoplast that might be less permissive for Pst DC3000 growth despite heat-weakened SA output. Finally, I explored the translation of our finding to crops. Tomato (Micro-Tom, Rio Grande-PtoS) did not exhibit HIS to Pst DC3000 at HT, underscoring pathosystem specificity. In rice (Kitaake), where HT enhances susceptibility to Xanthomonas oryzae pv. oryzae, a single foliar spray of the cytokinin antagonist PI-55 reduced lesion length without detectable growth or short-term yield penalties, evidence that transiently tuning down cytokinin perception can mitigate HIS in a crop. Together, our data support a nutrient-centric model: weakening cytokinin signaling under heat lowers apoplastic sugars while elevating branched-chain amino acids (BCAAs; valine, isoleucine), creating a niche less permissive to Pst DC3000. This BCAA-enriched, low-sugar state could explain the lack of HIS in ahk2,3 and points to PI-55 as a practical, non-transgenic lever for buffering disease risk in a warming climate.
Keywords: cytokinin signaling; plant hormones; plant–pathogen interactions; heat stress; apoplastic metabolomics; plant immune system